PENGELOLAAN DANA DESA DALAM UPAYA KESEJAHTERAAN MASYARAKAT DESA DALAM BINGKAI SIPAKATAU ASSAMATURU NA SIPAKALABBERE - Juliani Juliani; Sumarlin Sumarlin; Farid Fajrin (Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to find out how Tabbinjai Village exemplifies financial transparency and accountability, and reveals the role of sipakatau, assamaturu, and sipakalebbere values in fostering accountability and transparency in village financial management for the benefit of village communities.In this study, the type of qualitative phenomenological research was used. The type of data used is subject data obtained through interview-based data collection. By using triangulation of data sources to test the validity of the data obtained.The results of this study indicate that the Tabbinjai village government is in accordance with the principles of good governance, so it can be seen that the financial management of Tabbinjai Village is quite accountable, with direct accountability to interested parties and reporting on the implementation of the Village Budget. To ensure that financial management in Tabbinjai Village is not disrupted, the government ensures financial transparency by providing billboards, information boards, and open government performance evaluations that can be accessed by anyone. The implementation of local wisdom values of sipakatau, assamaturu, na sipakalabbere in Tabbinjai village has been applied in community life, especially in managing village funds, although there are still some obstacles faced..